2015
DOI: 10.1038/sc.2015.123
|View full text |Cite
|
Sign up to set email alerts
|

A new method for characterizing hand dysfunction in cervical spondylotic myelopathy: a preliminary study

Abstract: Study design: A case-control investigation. Objectives: The objective of this study was to quantitatively study impaired ability to appropriately adjust pinch strength while holding a small object in patients with cervical spondylotic myelopathy (CSM). Setting: Kochi Medical School Hospital, Japan. Methods: The subjects consisted of 19 CSM patients who had frequent episodes of failing to grasp and hold small objects in their daily life (Group A), 13 CSM patients who did not experience such episodes (Group B) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Degeneration does not necessarily occur in the anterograde direction only, and retrograde degeneration also occurs; however, antegrade Wallerian degeneration could explain the location of the pathologic change based on the positional relation with the lesion [ 15 ]. FC is an ascending tract that transmits proprioceptive and cutaneous feedback signals to the upper extremities; therefore, the group difference above the level of the lesion, which was confirmed in our study, was consistent with previous studies [ 47 , 48 ]. However, we were unable to explain why the DTI values of some tracts were better in patients than in the controls because this phenomenon has not been previously reported.…”
Section: Discussionsupporting
confidence: 93%
“…Degeneration does not necessarily occur in the anterograde direction only, and retrograde degeneration also occurs; however, antegrade Wallerian degeneration could explain the location of the pathologic change based on the positional relation with the lesion [ 15 ]. FC is an ascending tract that transmits proprioceptive and cutaneous feedback signals to the upper extremities; therefore, the group difference above the level of the lesion, which was confirmed in our study, was consistent with previous studies [ 47 , 48 ]. However, we were unable to explain why the DTI values of some tracts were better in patients than in the controls because this phenomenon has not been previously reported.…”
Section: Discussionsupporting
confidence: 93%
“…Doita et al reported a direct relationship between clinical myelopathy and proprioceptive ability in a hand function test [22]. In a study comparing CSM patients and normal controls, Akutagawa et al, found that myelopathy patients required a higher pinch pressure to grasp and hold small objects [23]. These studies suggest that impairment of the hand may be related to injuries to both the motor and sensory spinal tracts of the cervical spinal cord.…”
Section: Resultsmentioning
confidence: 99%
“…Degenerative cervical myelopathy (DCM) is the most common cause of non-traumatic neurological dysfunction of the spinal cord in adults [1]. The degenerative changes that occur in this condition involve the intervertebral discs, vertebral bodies, facet joints, hypertrophy of the ligamentum flavum, and ossification of the posterior longitudinal ligament (OPLL) [2].…”
Section: Introductionmentioning
confidence: 99%